Performance Analysis of Annular Fin Arrays with Forced Convection - Kumbhar, S. V.; Jadhav, M. A.; Chipare, P. G.; Kamble, G. G. (Asian Review of Mechanical Engineering, 2018)
Fins or extended surfaces are used whenever the available surface is found inadequate to transfer required heat with available temperature drop. These fins are not only chosen for their thermal performance, but also for other parameters such as weight, cost, reliability, etc. which depends upon application. The present paper mainly focuses on comparative analysis of plain annular fin arrays and perforated annular fin arrays to investigate heat transfer characteristics with forced convection. The data used in this performance analysis were obtained experimentally for annular fin arrays with and without perforation for aluminum. It is found that there is considerable change in heat transfer coefficient by 6.3 to 9.6% in case of perforated fin arrays which is a significant amount of increase in heat transfer rate.